New public management in India - Monga, Anil (2008)
Public Administrations, under the influence of New Public Management (NPM) wave have introduced series of measures to make them more open, transparent, accountable and responsive all over the world. Government in India, in tune with these global trends, has launched number of initiatives. The present study makes an attempt to review these initiatives and examine their impact on administrative systems. The study concludes that mindless adoption of all the elements of NPM would prove counterproductive in developing countries like India. - Reproduced.
Keywords: Public administration - India; Public administration